Oil-water separation using surface engineered superhydrophobic and superoleophilic membrane for the production of clean water. (February 2022) - Baig, Umair; Gondal, M.A.; Dastageer, M.A.
Abstract: Oil water separating membranes, exhibiting contrasting wetting characteristics for oil and water (superhydrophobicity, and superoleophility) were fabricated by dip coating different concentrations (5%, 10% and 20%) of trichloro(octadecyl)silane on the micro porous stainless steel mesh. The static contact angles of the fabricated surface in solid-air-water, and solid- air-oil interfaces are found to be 152° and 0° respectively. When trichloro(octadecyl)silane coated stainless steel membrane was used as a separating medium in the gravity driven oil water separating system, 99% oil-water separating efficiency was achieved in a single pass, and in addition to this, the fabricated membrane retained its wetting characteristics and oil water separating efficiency, even after 10 consecutive passes of oily water through the membrane. When the oily water comes in contact with the surface of the separating membrane, the water solid interface gets into Cassie-Baxter wetting state, where the air in the micro/nano structured pits renders low affinity of water on the membrane surface, whereas the surface roughness enhances the affinity of oil on the solid surface, and hence the coated surface attracts the oil phase to the pore boundaries of the mesh, and at the same time pushes the water phase to the top. The morphological characteristics and the elemental composition with FE-SEM, EDS, Elemental mapping and XPS characterizations, and the surface wettability of the coated membrane by measuring the interfacial contact angles were also carried out. Graphical abstract: Unlabelled Image